PENGARUH MOTIVASI KERJA, KEPEMIMPINAN, BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWANHOTELPANDANARANSEMARANG - Dennovita Ratna Utami; Tri Endang Yani (Solusi, 2020)
Assumption from this research reflected in hypothesis that suspects that there is a positive and significant of motivation, leadership, organizational culture and work environment to work performance. For testing the validity from that hypothesis it's needen a related data from worker opinion about motivation, leadership, organizational culture, work environment and work performance. Data explored based on judgement and worker opinion from 80 respondents.The result of the regression analysis is mean while Fis 49,326 with significant 0,00, If 0,710. So the variabel can explain 71% to performance and the rest 29% can be explained the other variables. From the research it can be concluded that motivation, leadership, organizational culture and work environment have positive influence to performance.Keyword : motivation, leadership, organizational culture, work environment and performance